Effects of microstructure on fracture strength and conductivity of sintered NMC333. Issue 3 (17th October 2019) - Huddleston, William; Dynys, Frederick; Sehirlioglu, Alp
Abstract: Sintering of LiNi0.33 Mn0.33 Co0.33 O2 cathode material was investigated for potential application in all‐electric aerospace propulsion systems utilizing new architectural concepts. All‐solid‐state batteries, while inherently safe, may not reach the high energy density required for next generation propulsion systems. To meet this performance requirement, multifunctionality of sintered active material may achieve systems level weight savings through simultaneous load bearing and electrochemical energy storage performance. The effects of sintering conditions on structural stability, chemistry, densification, grain size, fracture strength and electrical conductivity were quantified for the active cathode material. X‐ray diffraction and inductively coupled plasma results indicated the structure and stoichiometry were maintained across the range of processing conditions to facilitate intercalation. Densification was achieved by sintering at 1050°C in ambient atmosphere, but grain coarsening was observed for higher temperatures and longer hold times. Mechanical strength was improved with reduction in porosity, but excessive grain growth decreased strength, providing a maximum of 50 MPa for samples sintered at 1050°C for 10 hours. Electrical conductivity initially improved with densification, but significantly diminished as the microstructure coarsened. The optimal sintering condition of 1050°C maximized mechanical fracture strength and electrical conductivity, with shorter sintering times preferred.